Una mirada desde el margen: el caso de la infanticida María Mancilla (Buenos Aires, 1904) - Calandria, María Sol (2014)
This article intends to rebuild, from a microhistorical analysis and gender perspective, the experience of all mothers in the Buenos Aires province area at the beginning of the twentieth century. Through María Mancilla lifeline, we will look at the tensions and contradictions that stayed present during the discussion of the infanticide judicial sentences, were women questioned and resisted to what was established from the government in regards of the women/mother relation. In that sense, it is in the social practices field that we find the resistance and tensions that went beyond the attempts to normalize the generic practices and ideas. On the same way, her experience shows the agency feature that the party had, not as unified or autonomus individuals but as a party that wasnborn through the all the situations and the status that society gave to them.